Modifikasi Pupuk Urea Pelepasan Terkendali dan Pengaruhnya terhadap Lingkungan - Jayanudin Jayanudin; Retno S.D. Lestari; Muhammad Luthfi; Maulana Suyuti (BRIN Publishing (Penerbit BRIN), 2022)
Controlled release urea fertilizer is one solution to increase the efficiency of nutrient absorption by plants and is more environmentally friendly. The aims of this study was to determine the yield and water absorption of controlled release urea fertilizer and analyze the content of nitrate, nitrite, and ammonia as environmental pollution parameters. Controlled release urea fertilizer was prepared using the emulsion crosslinking method with chitosan as the matrix. Urea was dissolved in chitosan then added in oil and stirred to form an emulsion. Next, glutaraldehyde saturated toluene (GST) as a crosslinker was dripped slowly and then continuously stirred for 2 hours. Urea loaded-chitosan microspheres (controlled release urea fertilizer) were dried and analyzed. Furthermore, the yield, water absorption, and analysis of nitrate, nitrite, and ammonia from the released urea was determined. Controlled release urea fertilizer obtained yield was 91.3–97.28%, water absorption of 78.87–91.61%. Analysis of nitrate, nitrite, and ammonia from the study concluded that urea fertilizer contained in chitosan microspheres is more environmentally friendly.